2016
DOI: 10.1186/s13099-016-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Duck gut viral metagenome analysis captures snapshot of viral diversity

Abstract: BackgroundDucks (Anas platyrhynchos) an economically important waterfowl for meat, eggs and feathers; is also a natural reservoir for influenza A viruses. The emergence of novel viruses is attributed to the status of co-existence of multiple types and subtypes of viruses in the reservoir hosts. For effective prediction of future viral epidemic or pandemic an in-depth understanding of the virome status in the key reservoir species is highly essential.MethodsTo obtain an unbiased measure of viral diversity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
3
23
2
Order By: Relevance
“…The four strains contained the five phage viruses as follows: myoviruses, siphoviruses, podoviruses, inoviruses, and microviruses. This was consistent with the previously reported phage composition of ducks, human, pig, and equine feces by metagenomic analysis [11,13,[24][25][26]. A high percentage (99.43, 69.17, 95, 97.68%) of phage reads was double-stranded DNA viruses and belonged to the order Caudovirales, while the B strain had a higher percentage of inovirus reads than the A, C, or D strains.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The four strains contained the five phage viruses as follows: myoviruses, siphoviruses, podoviruses, inoviruses, and microviruses. This was consistent with the previously reported phage composition of ducks, human, pig, and equine feces by metagenomic analysis [11,13,[24][25][26]. A high percentage (99.43, 69.17, 95, 97.68%) of phage reads was double-stranded DNA viruses and belonged to the order Caudovirales, while the B strain had a higher percentage of inovirus reads than the A, C, or D strains.…”
Section: Discussionsupporting
confidence: 91%
“…Duck circovirus reads were detected in the B strain. Anatid herpesvirus 1, known as DPV, Fowlpox virus, Canarypox virus, and pigeonpox virus reads related to duck were found and relatively scarce, and those viral reads were identified in Indian ducks feces [13]. The result suggested that the sensitivity of PCR was not high; we should adopt a variety of methods to identify pathogens in samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of viromes of duck guts has been reported recently and 18 classified viral families were identified (Fawaz et al, 2016). Seven of these 18 families (Circoviridae, Dicistroviridae, Iflaviridae, Parvoviridae, Picornaviridae, Phycodnaviridae, and Virgaviridae) were also identified in the duck feces sample through this study.…”
Section: Discussionsupporting
confidence: 59%
“…Most importantly for veterinarians, RNA virus metagenomics has revealed a number of candidate etiological agents for a variety of animal ailments including avian proventricular dilatation disease, mink shaking syndrome, snake inclusion body disease, python respiratory illness, dairy cow disease, and tilapia die-offs (Kistler et al, 2008;Gancz et al, 2009;Blomström et al, 2010;Stenglein et al, 2014Stenglein et al, , 2012Uccellini et al, 2014;Hoffmann et al, 2012;Bacharach et al, 2016). Animal feces has proven fruitful hunting for metagenomicists, with canine, feline, porcine, equine, goose, duck, and shrew fecal RNA viromes turning up a plethora of mostly novel picorna-like viruses, albeit with an unclear relationship to disease and perhaps some more closely linked to the invertebrates indicated above (Fawaz et al, 2016;Greninger and Jerome, 2016;Li et al, 2011;Moreno et al, 2017;Nagai et al, 2015;Ng et al, 2014b;Phan et al, 2011;Reuter et al, 2012;Sano et al, 2016;Sasaki et al, 2015;Zhang et al, 2014). The recovery of Ancient Northwest Territories cripavirus from 700-year old frozen caribou feces illustrated an incredible stability of encapsidated RNA (Ng et al, 2014a).…”
Section: Bat-guano Crazy About Samplingmentioning
confidence: 99%